2014
DOI: 10.1377/hlthaff.2013.1297
|View full text |Cite
|
Sign up to set email alerts
|

HIV Care Providers Emphasize The Importance Of The Ryan White Program For Access To And Quality Of Care

Abstract: With the implementation of the Affordable Care Act (ACA) under way, some policy makers have questioned the continued relevance of the Ryan White HIV/AIDS Program as a safety net for people living with HIV/AIDS. We surveyed HIV care providers to understand the role of the Ryan White Program and to identify concerns regarding the ACA implementation. We also addressed whether the program is still relevant after ACA implementation and, if so, what elements should be retained. We found that providers consider the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…A systematic review of physician survey response bias indicates the amount of bias may be minimal (9). In the present study, the effective response rate was consistent with rates observed in unsolicited physician surveys (10). Demographic differences between survey responders and non-responders were generally small, with the exception that responders treated more patients receiving antipsychotic medication than non-responders.…”
Section: Discussionsupporting
confidence: 90%
“…A systematic review of physician survey response bias indicates the amount of bias may be minimal (9). In the present study, the effective response rate was consistent with rates observed in unsolicited physician surveys (10). Demographic differences between survey responders and non-responders were generally small, with the exception that responders treated more patients receiving antipsychotic medication than non-responders.…”
Section: Discussionsupporting
confidence: 90%
“…Second, these findings suggest that replacing HIV-infected persons’ RWHAP assistance with private insurance or Medicaid alone may not be optimal in terms of treatment outcomes. Last, transitions from RWHAP assistance to other coverage types are likely to be complicated by variable drug formularies, levels of provider expertise, and cost-sharing requirements, all of which could affect patient adherence and, ultimately, viral suppression [12]. RWHAP supplementation to private insurance or Medicaid may be one solution.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways include provision of medications, core medical and nonmedical case management, and supportive services such as substance abuse counseling, which are needed to promote ART treatment adherence, viral suppression, and overall health [9, 20, 21]. Importantly, RWHAP facilitates provision of these medical and supportive services using a coordinated approach similar to that of the medical home model, and many health providers in RWHAP facilities see HIV-infected patients exclusively [8, 12]. Patients with RWHAP only may have been more likely than those with other payer types, including those receiving supplemental RWHAP assistance, to receive coordinated care from RWHAP facilities serving as medical homes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, data from the most recent RWHAP Annual Client-Level Data Report [47] indicates that a quarter of PLWH in the US still lack health insurance, highlighting the need for continued funding of the program. In light of the RWHAP’s significant role in providing HIV care to PLWH in the US, current literature urges HIV providers to advocate for continued funding of RWHAP [5053], which has not been reauthorized since 2013 and relies on yearly appropriations from Congress [54]. …”
Section: Reviewmentioning
confidence: 99%